Prolactin gene diversity and its influence on milk yield traits in Ayrshire dairy cattle from Southern Russia (Journal of Advanced Veterinary and Animal Research, 2026)
Objective: The objective of this research was to discover single-nucleotide variations in the prolactin (PRL) gene and to evaluate their correlation with milk production characteristics in Ayrshire cows reared in southern Russia. Materials and Methods: DNA (deoxyribonucleic acid) samples were extracted from the blood of cows (n = 300) using a commercial kit. The polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) technique was employed to identify and quantify genotypes and allele frequencies. Genetic indices were calculated, and statistical processing was performed. A general linear model was used to investigate the relationship between single-nucleotide polymorphisms and milk productivity in cows. Results: The distribution of the AA, AB, and BB genotypes in the studied population was 90%, 0%, and 10%, respectively. The genetic equilibrium in the Ayrshire cow population was preserved (χ² = 0.2879). The results indicate the presence of allelic diversity in the prolactin gene in this population. The milk yield per lactation in cows with the PRL_AA genotype was 7,378.50 kg, and for PRL_BB, it was 6,569.63 kg. Ayrshire cows with the PRL_BB genotype yielded less milk compared to their PRL_AA counterparts by 10.96% (p < 0.05). Conclusion: Using the obtained results in the future selection of offspring with desirable PRL genotypes at an earlier age could significantly increase the efficiency of breeding work in the studpulation and accelerate the process of creating a herd with higher productivity potential.J. Adv. Vet. Anim. Res., 12(4): 1125–1131, December 2025http://doi.org/10.5455/javar.2025.l973